PERBANYAKAN ANGGREK Dendrobium heterocarpum Lindl. SECARA IN VITRO DENGAN MEDIA YANG BERBEDA - Setiawati, Yuli; Astarini, Ida Ayu; Astiti, Ni Putu Adriani (Metamorfosa: Journal of Biological Sciences; Vol 2 No 1 (2015), 2015)
Dendrobium heterocarpum Lindl. is one of the orchid species which is often seeked. It is because this species has a mystique appearance and special fragrance. The research aimed to observe the growth and developing responses of protocorm like bodies (PLBs) of D. heterocarpum after 12 weeks in three different medium, i.e. Murashige and Skoog (MS), Kursor C and Western 3 (W3). The D. heterocarpum seeds were planted in MS, Kursor C and W3 medium. Qualitatively the orchid growth were observe including growth score and colour score. The result showed that growing time of MS was 4 weeks, a week faster than the growing time on Kursor C and W3 medium. The growing phase on MS medium and Kursor C medium reached phase 1 whereas on W3 medium reached phase 2. PLB’s colour after 12 weeks on MS medium reached phase E, strong yellowish green phase (142A). Meanwhile, on Kursor C and W3 was on phase D, moderate yellowish green (143D).
Keywords: Dendrobium heterocarpum Lindl, MS, Kursor C, W3, in vitro